The adventures of Tom Sawyer - Thomas, Patricia; Twain, Mark (Voida, UP : Wisemen World Classics, 2010)
Whether tricking other boys into doing his work or sneaking off to bury a dead cat, Tom Sawyer is a boy with a fondness for mischief. But things become grim when he and his pal Huck Finn witness a murder and cover-up by the lawless Injun Joe. Even though he's scared the murderer will come after him next, Tom continues to explore the Missouri countryside with his friends and attempts to woo the new girl in town.
Keywords: Boys -- Missouri -- Fiction; Action and adventure fiction